Healthcare resource utilisation and sickness absence in newly diagnosed multiple myeloma patients who did not undergo autologous stem cell transplantation: Trends in Sweden with the changing treatment landscape. (5th May 2021) - Borgsten, Fredrik; Gatopoulou, Xenia; Pisini, Marta; Tambour, Magnus; Schain, Frida; Jones, Christina V.; Kwok, Kelvin Ho Man; Batyrbekova, Nurgul; Björkholm, Magnus
Abstract: Objectives: The introduction of novel drugs has significantly improved outcomes for multiple myeloma (MM) patients. This study describes survival, healthcare resource utilisation and sickness absence in association with the changing MM treatment landscape over time, focussing on patients who did not undergo autologous stem cell transplantation (ASCT). Methods: Population‐based, retrospective registry study in Sweden, where 7012 non‐ASCT patients diagnosed between 2001 and 2015 were stratified into diagnosis periods 2001‐2005 (n = 2053), 2006‐2010 (n = 2372) and 2011‐2015 (n = 2587). Results: Median survival increased from 2.5 to 3.4 years from 2001‐2005 to 2011‐2015. During the first 3 years of follow‐up, patients diagnosed during 2011‐2015 spent 29% and 12% less time in health care (55 days; inpatient admissions and outpatient visits) than patients diagnosed during 2001‐2005 (78 days) and 2006‐2010 (63 days), respectively. This was associated with less inpatient and more outpatient healthcare usage. Average 3‐year sickness absence (362 days) was 31% and 12% less than for patients diagnosed during 2001‐2005 (522 days) and 2006‐2010 (410 days), respectively. Conclusions: These findings of improved survival, reduced healthcare needs and greater productivity in non‐ASCT MM patients with access to improved treatment practices and novel drugs provide important real‐world cost‐benefit insights for the continued development and introduction of treatments for MM.